(untitled) (Journal of Engineering, 2011)
Physical model tests were simulated non-aqueous phase liquid (NAPL) spill in two-dimensional domain above the water table. Four laboratory experiments were carried out in the sand-filled tank. The evolution of the plume was observed through the transparent side of this tank and the contaminant front was traced at appropriate intervals. The materials used in these experiments were Al-Najaf sand as a porous medium and kerosene as contaminant. The results of the experiments showed that after kerosene spreading comes to a halt (ceased) in the homogeneous sand, the bulk of this contaminant is contained within a pancake-shaped lens situated on top of the capillary fringe.